Individualized and Fixed Thresholds to Demarcate PlayerLoad Intensity Zones Produce Different Outcomes. Issue 7 (July 2021) - Scanlan, Aaron T.; Fox, Jordan L.; Milanović, Zoran; Stojanović, Emilija; Stanton, Robert; Dalbo, Vincent J.
Abstract : Abstract: Scanlan, AT, Fox, JL, Milanović, Z, Stojanović, E, Stanton, R, and Dalbo, VJ. Individualized and fixed thresholds to demarcate PlayerLoad intensity zones produce different outcomes. J Strength Cond Res 35(7): 2046–2052, 2021—Individualized approaches to derive intensity zones are yet to be examined using microsensor metrics in basketball. The purpose of this study was to quantify and compare the time spent in different PlayerLoad intensity zones using individualized and fixed approaches during basketball training. Thirteen semiprofessional, male basketball players were monitored across the preparatory training phase. Microsensors recorded the time spent in 6 PlayerLoad intensity zones using individualized and fixed approaches. Individualized zones were calculated relative to the peak instantaneous PlayerLoad response observed in each player across training. Fixed zones were determined following predefined cut-points set in proprietary software. The majority of training time was spent in zones 1–2 (98–99%), with a low proportion of time detected in zones 3–6 (1–2%) across approaches. The fixed approach produced greater training time in zones 2 (11.9 ± 1.2 vs. 9.3 ± 2.4 minutes; very likely large) and 3 (1.7 ± 0.8 vs. 0.8 ± 0.9 minutes; very likely moderate), was an unclear small increase in time spent in zone 1 were apparent using individualized thresholds (76.5 ± 11.2 vs. 72.9 ± 9.6 minutes). Almost certain similar time was spent in zones 4–6 across approaches. Individual analyses showed deviations across players; however, fixed PlayerLoad thresholds produced higher training time in zones 2 (moderate to very large), 3 (moderate to very large), 4 (moderate to large), and 5 (moderate) than the individualized approach in most players. Variations in outcomes between individualized and fixed approaches must be considered when quantifying the time spent working in PlayerLoad intensity zones.